Senegal : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper estimates the macroeconomic impact of these discoveries and discusses potential fiscal frameworks for managing related revenues. Pre-production investment (2019-2021) will lead to an increase in the current account deficit; however, this will be followed by a boost to exports as hydrocarbon production comes online (2022 onward). Discoveries are important but will not lead to a major transformation of the economy, with hydrocarbons expected to make up not more than 5 percent of GDP. Fiscal revenues would average about 1.5 percent of GDP over a 25-year period and about 3 percent of GDP when production peaks. Given the relatively small gains in revenue, IMF staff recommends a fiscal framework that allows for an initial drawdown of government resources to finance large up-front investment needs, followed by an appropriate target level of the non-resource primary balance which is to serve as a medium-term fiscal anchor. Issues related to managing the volatility of resource revenues are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet